Accuracy of Cervical Intraepithelial Lesion Diagnosis by Visual Cervical Examination with Acetic Acid - Uzma Latif, Najma Bibi, Maria Ghafoor, Rubina Babar, Fauzia Anbreen, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Using acetic acid to inspect the vaginal canal is a simple screening procedure done with the naked eye. During a speculum examination, the cervical transformation zone is painted with acetic acid 3% to 5% or vinegar. It is a simple, cost-effective screening tool that can be used in poor developing countries with high rates of invasive cervical cancer mortality because acetic acid coagulates nuclear proteins, resulting in white discoloration of the transformation zone in CIN and early invasive cancer. Objective: This study aims to measure the effectiveness of a simple and economical screening test, visual inspection with acetic acid (VIA), for diagnosing cervical intraepithelial lesions in comparison to the gold standard of histopathology using a study population of women attending a gynecology outpatient department. Study Design: The study used a cross-sectional design to validate the findings. Study Area: This study was conducted in the Obstetrics & Gynecology Department, Women and Children Teaching Hospital, Dera Ismail Khan. Study Duration: This study took place between November 2018 and April 2019. Materials and Methods: The study included 414 women with abnormal vaginal bleeding. Under a good light source, a lubricated Cusco's speculum was introduced into the vagina to evaluate the cervix for gross abnormalities. A cotton swab was used to apply 3% acetic acid to the cervix and acetowhite changes were observed for one minute. Positive results were considered when distinct acetowhite areas were detected, while negative results were considered when light, faint, or doubtful aceto-white areas were detected. Results: There was a range of age from 18 to 40 years in this study with a mean age of 30.772 years and a mean weight of 71.644 kilograms. For diagnosis of cervical intraepithelial lesions, acetic acid visual examination has shown a sensitivity of 84.38%, specificity of 97.11%, diagnostic accuracy of 95%, PPV of 84.38%, and NPV of 97.11% (p=0.000). Practical implication: The purpose of this study is to compare the efficacy of a simple and inexpensive screening test, visual inspection with acetic acid (VIA), to the gold standard of histopathology in a study group of women attending a gynecological outpatient service. Cervical cancer is a leading cause of death among women in developing countries, where access to advanced diagnostic tools is limited. If VIA proves to be an effective screening tool, it could be widely implemented in low-resource settings to improve early detection and treatment of cervical cancer. Conclusion: VIA is considered an appropriate screening alternative for a large population. In contrast to cytology-based programs, it is highly sensitive, low-cost, and yields immediate results. Keywords: Cervical Cancer; Visual Inspection with Acetic Acid; Screening